Resilience as an urban strategy: The role of green interventions in recovery plans - Federica Gaglione; David Ania Ayiine-Etigo (TeMA: Journal of Land Use, Mobility and Environment, 2021)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always following a rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is a continuous update about emerging topics concerning relationships among urban planning, mobility and environment thanks to a collection of short scientific papers written by young researchers. The Review Notes are made up of five parts. Each section examines a specific aspect of the broader information storage within the main interests of the TeMA Journal. In particular: the Town Planning International Rules and Legislation Overview section aims at presenting the latest updates in the territorial and urban legislative sphere. The issue of the current recovery and resilience plans and the related reforms envisaged in them aim to give impetus to new forms of organization of urban systems and all its components. In this direction, the content of this review describes the reforms envisaged in the National Recovery and Resilience Plan of Italy and Germany with a focus on the due mission based on the green revolution and ecological transition. Furthermore, this review aims to define the role of these plans for future urban strategies to face the great challenges to which cities are called to respond such as climate change, energy efficiency while also respecting the principles of environmental sustainability.